2010
DOI: 10.1016/j.cell.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Pausing of RNA Polymerase II Disrupts DNA-Specified Nucleosome Organization to Enable Precise Gene Regulation

Abstract: Metazoan transcription is controlled either through coordinated recruitment of transcription machinery to the gene promoter, or through regulated pausing of RNA polymerase II (Pol II) in early elongation. We report that a striking difference between genes that use these distinct regulatory strategies lies in the “default” chromatin architecture specified by their DNA sequences. Pol II pausing is prominent at highly-regulated genes whose sequences inherently disfavor nucleosome formation within the gene, but fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

69
511
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(581 citation statements)
references
References 50 publications
69
511
1
Order By: Relevance
“…Others have made similar suggestions; for example, paused Pol II has been argued to compete with histones for occupancy of highly regulated promoters in mammalian cells (71). To test the role of the PIC in histone eviction, we examined the effect of mutations in PIC components TBP and Pol II on histone association at various promoters.…”
Section: Discussionmentioning
confidence: 92%
“…Others have made similar suggestions; for example, paused Pol II has been argued to compete with histones for occupancy of highly regulated promoters in mammalian cells (71). To test the role of the PIC in histone eviction, we examined the effect of mutations in PIC components TBP and Pol II on histone association at various promoters.…”
Section: Discussionmentioning
confidence: 92%
“…129,130 Indeed, genes bound by DSIF and NELF significantly overlap (> 90%) with those bound by Pol II. 97,131,132 Finally, functional data supports this model, as incubation of HeLa cells with flavopiridol, an inhibitor of P-TEFb, reduces the level of transcription to a level strikingly similar to incubation with α-amanitin, a well-studied Pol II inhibitor. 133 Thus, P-TEFb-mediated DSIF/NELF release is a generally required and regulated step of transcription in higher eukaryotes.…”
Section: Pol II Elongation Is a General Step Of Transcription Regulatmentioning
confidence: 71%
“…Previous work showed that the transcription of these genes does not require CSB (24). The difference between these gene families may lie in the fact that stress-response gene promoters are preassembled, awaiting for a stimulus to start elongation, whereas NR-inducible and HK genes must undergo cycles or assembly and disassembly (24,29,30,(43)(44)(45).…”
Section: Sirt1 Mediates Repression Of Hk Genes In Xp-d/cs Cells After Uvmentioning
confidence: 99%